Energy factor in Italy’s policy in the Mediterranean and in the Middle East - Vasilkov, Vladimir V. (Journal of the Belarusian State University. International Relations, 2021)
The article examines Italy’s attempts to implement a number of tasks of its energy strategy through foreign policy tools in the traditionally important for this country the Mediterranean and the Middle East region. It has been predicted that the importance of this region (including the South Caucasus) for Italian geopolitical interests in the coming years will increase even more because of the taken governmental course to diminish coal consumption, as well as the need to diversify the channels of natural gas supply to the country, taking into account the reduction in gas production by the Netherlands and interruptions in gas supplies from Russia.
Keywords: Italy; Italian foreign policy; Mediterranean; energy; Transadriatic gas pipeline; Eastern Mediterranean gas pipeline; Poseidon; Libya; “Iranian dossier”; South Caucasus